Kepribadian Kolektif: Kebudayaan Membentuk Pola Berpikir dan Perilaku dalam Masyarakat - Fitriani, Salwiyah; Dana, Tri Rahma; Sari, Purnama; Putri, Tri Nur; Sa’diyah, Halimatus (Indra institute Research & Publication, 2025)
Collective personality refers to the shared patterns of thinking, values, and behavior possessed by members of a society or social group. This article aims to analyze the role of culture in shaping collective personality, as well as how culture influences the thinking patterns and behaviors of individuals within a society. Using the approaches of sociology and social anthropology, this study identifies the impact of cultural norms, belief systems, and traditions in shaping a collective social identity. The culture accepted by a society not only determines the worldview but also directs how individuals interact, communicate, and behave in social life. By examining various examples of different societies, this study reveals the variations in thinking patterns and behaviors influenced by each society's culture, as well as how this shapes solidarity and social cohesion within these groups. The article concludes that the culture of a society plays a crucial role in shaping the collective personality, which in turn affects social dynamics and interpersonal relationships within the community.